Zur Rezeption der Dramen von Friedrich Schiller im geteilten Polen. Schillers Dramen auf den Bühnen in Warschau in den Jahren 1803-1918 - Cabańska-Czekańska, Małgorzata (Studia Germanica Posnaniensia, 2018)
Analysis of the process of theoretical reception of F. Schiller's dramas in Warsaw during the partitions is a part of an extensive study on all forms of reception of dramas of the German classic author in Polish circles of readers in Poland at about 1800 and until the recent times. The history of staging Schiller's dramas was in the Russian partition most strongly influenced by the political factor, like for instance, the context of both national uprisings (positive factor) and the repressions of the Tsarist authorities resulting from them. The decisive influence on the position of F. Schiller's drama in the theatres of Warsaw was the activity of W. Bogusławski and the eminent actors as well as literary refinement of Polish magnates, noblemen and powerful intelligentsia.